Merging photoredox with copper catalysis: decarboxylative difluoroacetylation of α, β-unsaturated carboxylic acids with ICF2CO2Et. Issue 79 (13th September 2016) - Zhang, Heng-Rui; Chen, Dao-Qian; Han, Ya-Ping; Qiu, Yi-Feng; Jin, Dong-Po; Liu, Xue-Yuan
Abstract : A novel decarboxylative difluoroacetylation of α, β-unsaturated carboxylic acids via a combination of visible light photocatalysis and cooper catalysis is reported. Abstract : A photoredox-/copper-catalyzed decarboxylative difluoroacetylation reaction of α, β-unsaturated carboxylic acids has been developed. This reaction produces a variety of difluoroalkylated alkenes in moderate to excellent yields and exhibits satisfactory stereoselectivity and a broad substrate scope at ambient temperature. Furthermore, this decarboxylative difluoroacetylation protocol provides efficient and environment friendly access to the difluoroalkylated alkenes.